Pathopolitics: Pathologies and Biopolitics of PrEP - Atuk, Tankut (Frontiers in Sociology, 2020)
This paper unveils the pathologies that are produced and sustained by the pharmaceutical industry, specifically by Gilead Sciences, Inc. Broadly defined, pathopolitics is the politics of treating and/or reproducing pathologies. This paper examines pathopolitics in the context of PrEP, or pre-exposure prophylaxis, an antiretroviral medicine that prevents HIV transmission. Although Gilead promises to prevent a pathology through PrEP, it reproduces social and biological pathologies by exposing certain people to higher risks of infections and diseases, thus epitomizing the operating logic of the pharmaceutical industry: that life is protected only insofar as it offers surplus economic and social value. This essay raises three fundamental sets of questions: (1) What are the techniques and mechanics of pathopolitics? (2) How does the pharmaceutical industry produce and exploit surplus value? (3) What is the nature of the relationship between the pharmaceutical citizenship and pathopolitics?